2011
DOI: 10.1016/j.compscitech.2011.06.004
|View full text |Cite
|
Sign up to set email alerts
|

In situ fibre fracture measurement in carbon–epoxy laminates using high resolution computed tomography

Abstract: observed consisted of a group of eleven breaks and a group of fourteen breaks. The large clusters were observed at the highest load, at sites with no prior breaks, indicating they occurred within a relatively narrow load range. No strong correlation was found between the location of matrix damage and fibre breaks. The data achieved has been made available online at www.materialsdatacentre.com/ for ongoing model development and validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
186
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(206 citation statements)
references
References 28 publications
19
186
1
Order By: Relevance
“…Size effects at the macro-scale (n [i] 50) are governed by the WLT (Figure 11), which is consistent with the quasi-brittle nature of FRPs (Okabe and Takeda, 2002, Scott et al, 2011, Wisnom, 1999. A critical fibre break cluster -after which failure is catastrophic -is defined by the bundle size at which full model and WLT start converging (n [i] ≈ 50 for the nominal inputs in Table 1).…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Size effects at the macro-scale (n [i] 50) are governed by the WLT (Figure 11), which is consistent with the quasi-brittle nature of FRPs (Okabe and Takeda, 2002, Scott et al, 2011, Wisnom, 1999. A critical fibre break cluster -after which failure is catastrophic -is defined by the bundle size at which full model and WLT start converging (n [i] ≈ 50 for the nominal inputs in Table 1).…”
mentioning
confidence: 62%
“…Beyerlein and Phoenix (1996a) and Kazanci (2004) tested microbundles (with 4 and 7 fibres respectively) and found that bundle strengths deviated significantly from Weibull distributions; moreover, some bundles (depending on the resin) had higher mean strength than the single-fibres, but considerably lower variability. At the macroscopic scale, Okabe and Takeda (2002) and Scott et al (2011) observed several clusters of fibre breaks before final coupon failure. Wisnom (1999) also noted that both the magnitude of size effects and the variability of strength decrease for larger specimens.…”
Section: Introductionmentioning
confidence: 99%
“…When the strain is further increased, this increased probability will lead to the development of clusters of broken fibres (see Fig. 4c) [38]. If one of these clusters grows large enough and reaches a certain critical size, then that cluster will grow in an unstable manner and lead to final failure (see Fig.…”
Section: Failure Developmentmentioning
confidence: 99%
“…The 3D morphology of impact damage was segmented via the semi-automatic 'seed growth' approach [44] in the same 'matchstick' specimen using µCT and SRCT data, as shown in Fig. 6(a/b).…”
Section: D Segmentationmentioning
confidence: 99%
“…What is desirable is a technique that offers high resolution to study the internal micromechanical damage in 3D, without the issues of destroying the sample or introducing new damage. To achieve this, synchrotron radiation computed tomography (SRCT) [10][11][12][13][14], and in more recent work synchrotron radiation computed laminography (SRCL) [15,16] have been successfully used to study composite materials at voxel resolutions in the order of 1 micron and below. In comparison, laboratory microfocus computed tomography (µCT) offers routine moderate resolutions, typically several micrometers and above [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%